2017
DOI: 10.1371/journal.pone.0177344
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interaction between fetal adversity and a genetic score reflecting dopamine function on developmental outcomes at 36 months

Abstract: BackgroundFetal adversity, evidenced by poor fetal growth for instance, is associated with increased risk for several diseases later in life. Classical cut-offs to characterize small (SGA) and large for gestational age (LGA) newborns are used to define long term vulnerability. We aimed at exploring the possible dynamism of different birth weight cut-offs in defining vulnerability in developmental outcomes (through the Bayley Scales of Infant and Toddler Development), using the example of a gene vs. fetal adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…In total, 89 samples from 60 studies including 52 822 children compared preterm and term-born children who had IUGR and were SGA with children with AGA with respect to cognitive outcomes. A total of 48 studies reported results for mean cognitive scores, and 24 studies reported the percentages of group-specific children with BII …”
Section: Resultsmentioning
confidence: 99%
“…In total, 89 samples from 60 studies including 52 822 children compared preterm and term-born children who had IUGR and were SGA with children with AGA with respect to cognitive outcomes. A total of 48 studies reported results for mean cognitive scores, and 24 studies reported the percentages of group-specific children with BII …”
Section: Resultsmentioning
confidence: 99%
“…In this study we have found some distinct patterns of association between the continuum of birth weight and childhood obesogenic behaviors considering linear and quadratic distributions and sex[53]. Birth weight effects were more evident in boys, as compared to girls, especially for physical activity and screen time.…”
Section: Discussionmentioning
confidence: 96%
“…For our secondary aim, a total of 68 articles were considered eligible and included in this systematic review after two-stage screening, as shown in Figure 1. Among the final included studies that assessed cognitive or academic outcomes, 11 studies (see Table S3) only investigated the effect of LGA, [35][36][37][38][39][40][41][42][43][44][45] 51 studies (see Table S2) only investigated the effect of early-term delivery (37 +0 w-38 +6 w), 13, 23-26, 29, 46-90 and 6 studies (see Table S1) explored the effects of both exposures simultaneously but independently. 28,30,[91][92][93][94] Early-term delivery…”
Section: Study Selectionmentioning
confidence: 99%
“…Furthermore, different definitions were utilized for LGA or full-term across studies. For example, although most studies used greater than the 90th percentile as the definition of LGA, several studies used the 80th 40 or 85th 35,42 percentile as the definition. Although most studies used the 10-90 th percentile as the definition of AGA, some studies used other reference groups, e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%